CLINICAL EFFICIENCY OF VAGINAL TRAINING DEVICE IN TREATMENT OF PELVIC ORGAN PROLAPSE IN ELDERLY WOMEN - OLESYA S. Korotkevitch; IGOR A. Eizenakh; VADIM G. Mozes; IGOR S. Zakharov (Фундаментальная и клиническая медицина)
Aim. To evaluate the efficacy of vaginal training device in treatment of pelvic organ prolapse in elderly women.Materials and Methods. We consecutively recruited 49 elderly women with grade 1 pelvic prolapse and overt or occult urinary inconti-nence having strict contraindications for surgical treatment. Half of the patients (n = 24) were pre-scribed to the use of vaginal training device Yolana Phase 1 while another half (n = 25) utilized Kegel exercises for the training of pelvic floor muscles. Outcomes were studied 6 months after the start of treatment. The primary treatment outcome was the prevalence of overt or occult urinary incontinence diagnosed by cough test and Valsalva maneuver. Secondary treatment outcomes included pelvic pain, dyspareunia, degree of pelvic organ prolapse (Baden-Walker classification), and strength of the pelvic floor muscles defined by a cone test. Results. Patients who employed vaginal training device had a lower prevalence of urinary in-continence, pelvic pain, and dyspareunia and were generally characterized by a higher strength of the pelvic floor muscles, as compared to those who used Kegel exercises. Conclusions. Vaginal training devices are use-ful to increase strength of pelvic floor muscles in patients with grade 1 pelvic organ prolapse, decreasing both overt and occult urinary incontinence and improving other symptoms related to the quality of life.